Rural Ethnic Minority Youth and Families in the United States Theory, Research, and Applications - Crockett, Lisa J.; Carlo, Gustavo (Advancing Responsible Adolescent Development,, 2016)
This book explores the risk and protective factors of rural life and minority status for youth and their families. It provides innovative perspectives on well-documented developmental challenges (e.g., poverty and lack of resources) as well as insights into the benefits of familial and cultural strengths. Coverage includes recent theories in child development, empirical studies of rural minority populations, and leading-edge interventions for urgent issues. The volume presents a spectrum of opportunities for understanding and providing services for youth in the United States through the lens of a diverse collection of ethnic minority experiences in rural settings. Topics featured in this volume include: Theoretical models focused on the intersection of ethnicity and rural settings. Family processes, child care, and early schooling in rural minority families. Promising strategies for conducting research with rural minority families. Strengths-based educational interventions in rural settings. Promoting supportive contexts for minority youth in low-resource rural communities. Rural Ethnic Minority Youth and Families in the United States is a valuable resource for researchers and professors, clinicians and related professionals, and graduate students across such disciplines as clinical child, school, and developmental psychology, family studies, social work, and public health.  ------ "Bringing together cutting-edge scholarship in this watershed publication, Crockett and Carlo provide a singularly important foundation for future research seeking to describe, explain, and optimize the strengths of these still relatively understudied youth." Richard M. Lerner Bergstrom Chair in Applied Developmental Science Director, Institute for Applied Research in Youth Development Tufts University  "The authors integrate long-standing ideas about rural settings and contemporary knowledge about ethnic minority status to present a long overdue treatment of the development of ethnic minority youth in rural America. This volume sheds light on an understudied and neglected segment of the American population." Andrew J. Fuligni University of California, Los Angeles.